Correction: Triboelectric generator for wearable devices fabricated using a casting method. Issue 17 (3rd February 2016) - Lee, Chang Jun; Choi, A. Young; Park, Jiwon; Choi, Changsoon; Sim, Hyeon Jun; Kim, Seon Jeong; Kim, Youn Tae
Abstract : Correction for 'Triboelectric generator for wearable devices fabricated using a casting method' by Chang Jun Lee et al., RSC Adv., 2016, 6, 10094–10098.